Chemically modified cellulose nanofibril as an additive for two‐component polyurethane coatings. Issue 19 (23rd January 2017) - Virtanen, Sanna; Jämsä, Saila; Talja, Riku; Heikkinen, Harri; Vuoti, Sauli
ABSTRACT: The increasing demand for the use of sustainable materials in industrial applications has created an urge to develop technologies that enable the use of biopolymers such as cellulose for the improvement of properties of commercial products. In this study, the potential of the silyl functionalized cellulose nanofibrils (CNF) as a reinforcing additive for the water‐ and solvent‐based two‐component polyurethane (PU) lacquer coatings was evaluated. The addition of the silylated CNF improved the abrasion resistance, strength, and elasticity of the PU coatings. When using the silylated CNF as an additive, the adhesion of the PU coatings was retained. The oxygen permeation rate of the silylated CNF films was strongly influenced by the nature of the solvent. The silylated CNF showed potential as a reinforcing additive even at low loadings in the two‐component PU lacquers. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44801. Abstract :